H-bonding dependent phosphorescence in a mixed ligand copper(I) complex. (8th January 2018) - Durini, Sara; Ardizzoia, G. Attilio; Colombo, Gioele; Therrien, Bruno; Brenna, Stefano
Graphical abstract: The mixed ligand phosphorescent copper(I) complex [Cu(PPh3 )2 (lact)] (lact = l -lactate) has been synthesized and fully characterized both in solution and in the solid state. Evidences on the decisive role played by intermolecular hydrogen bonds in the emissive properties of the title compound are given. Abstract: The mixed ligand copper(I) derivative [Cu(PPh3 )2 (κ 2 -O, O″-lact)] (1 ) (lact = l -(+)-lactate) has been prepared and fully characterized. NMR studies indicated the occurrence of a fluxional behavior involving the lactate anion, in solution. The α-hydroxycarboxylate ligand is responsible for the generation of a catemeric O–H⋯O(CO) H-bonding network that strongly influences the photophysical properties of1, in the solid state. Indeed, when irradiated with UV light the title compound shows a bright phosphorescence, which as suggested by DFT calculations is strictly related to the abovementioned H-bonding network.